Análise de custos entre paredes de alvenaria e de concreto armado moldadas no local - Silva, Leonardo Edmur da (2021)
This work deals with a comparative study between a project’s cost analysis in masonry and molded concrete walls developed for a housing estate in Mega Park neighborhood, in Apucarana – PR for 40 units. The data intends obtaining informations about the systems, emphasizing its executives characteristics and methods along with its main advantages ans disadvantages, those developed through in-depth bibliographic and documentary research. For the costs comparison, a detailed synthetic budget was used for each systems involved and studied in this research in order to prove the viability of one of the constructive methods through comparisons between the data obtained.